The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1002/ejic.200390184
|View full text |Cite
|
Sign up to set email alerts
|

Arylcalcium Hydrides as Precursors to Alkoxides and Aryloxides of Calcium

Abstract: Calcium atoms react with +I-substituted benzene derivatives under cocondensation conditions to yield arylcalcium hydrides. With toluene, tert-butylbenzene, and trimethyl(phenyl)silane the reaction showed no selectivity for C−H activation, resulting in the formation of each of the three possible isomers, while with m-xylene the reaction resulted in selective activation of the bond meta to the CH 3 groups. Treatment of (tert-butylphenyl)calcium hydride with di-and trisubstituted phenols such as 2,6-di-tert-butyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…[22] The co-condensation of calcium with benzene and alkylbenzenes yielded the insertion products, namely the arylcalcium hydrides. [23,24] However, neither NMR data nor structural parameters were reported. [25] Only very recently, Harder published the first molecular structure of a heteroleptic organocalcium hydride.…”
Section: Introductionmentioning
confidence: 98%
“…[22] The co-condensation of calcium with benzene and alkylbenzenes yielded the insertion products, namely the arylcalcium hydrides. [23,24] However, neither NMR data nor structural parameters were reported. [25] Only very recently, Harder published the first molecular structure of a heteroleptic organocalcium hydride.…”
Section: Introductionmentioning
confidence: 98%
“…[34] The reported mean Rb-N bond length of 3.197 Å is close to the value for Rb1-N3 [3.0458(16) Å] in 3. Another compound with the composition [(tBuO) 8 Li 4 Rb 4 ] contains neither nitrogen nor phosphorus atoms, which is also the case with the other examples in the CSD. [35] Interestingly, there are two signals in the 7 Li{ 1 H} NMR spectrum of 3.…”
Section: Resultsmentioning
confidence: 78%
“…The use of benzyl calcium as a precatalysis for the hydrosilylation of 2-vinylpyridine has been studied by Souter et al [12] [a] Institut für Anorganische Chemie, Georg-August-Universität Göttingen, Tammannstr. 4 Heterobimetallic complexes have gained ever increasing attention in preparative chemistry, [9] above all for use in deprotonation reactions. Usually, lithium organic reagents like BuLi or LDA are used for such purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harder and co-workers demonstrated that R-Ca-H is a valuable synthon [5] for the hydrogenation of alkenes [6], an intermediate during hydrosilylation of ketones [7], and reacts also as a strong reducing reagent [8]. Phenylcalcium hydride (R = Ph) was prepared via a cocondensation reaction of calcium with benzene yielding extremely reactive PhCaH [9,10]. Stability of an organylcalcium hydride can be enhanced if R represents an extremely bulky β-diketiminate ligand which is able to prevent the precipitation of insoluble CaH 2 via a dismutation reaction [11].…”
mentioning
confidence: 99%